Jeunes Migrants Et Consommation De Drogues Dans La Region Du Haut-Sassandra En Cote dâ€™Ivoire (Daloa) - Marc, Ounnebo Gniondjibohoui; Daniel, Yao Kouakou; Kouakou, FranÃ§ois Yao (European Scientific Journal, ESJ, 2017)
The purpose of the present work was to identify the explanatory factors of drug use among young migrants in the Upper Sassandra region, particularly in Daloa. It combined a mixed approach using a questionnaire and interview guide to collect data from all stakeholders involved in the relationship between young migrant status and drug use. In this perspective, young migrants as well as institutional and community actors were interviewed the geographical field of the sub-districts of the city of Daloa which is presented by several works as a hub of immigration. The working hypothesis that the practice of drug use among young migrants in Daloa is determined by factors related to social, psychological and financial vulnerability related to this status is validated in this work.